Diaporthe species associated with twig blight and dieback of Vaccinium corymbosum in Portugal, with description of four new species. (3rd March 2020) - Hilário, Sandra; Amaral, Inês A.; Gonçalves, Micael F. M.; Lopes, Anabela; Santos, Liliana; Alves, Artur
ABSTRACT: Blueberry, an increasingly cultivated fruit crop in Portugal, is known to be susceptible to twig blight and dieback caused by species of Diaporthe . The diversity of Diaporthe species associated with symptomatic and asymptomatic Vaccinium corymbosum plants in Portugal was assessed. A multilocus sequence analysis of the rDNA internal transcribed spacer (ITS) region and the translation elongation factor 1-alpha ( tef1-α ), β-tubulin ( tub2 ), calmodulin ( cal ), and histone 3 ( his3 ) genes revealed the presence of Diaporthe foeniculina, Diaporthe rudis, and four new species, which are described as Diaporthe crousii, Diaporthe phillipsii, Diaporthe rossmaniae, and Diaporthe vacuae . These new species were characterized in terms of their morphology, mating strategies, and temperature growth requirements. In artificial inoculation trials of V. corymbosum cv. Bluecrop plants, all Diaporthe species caused minor symptoms. Further, no differences in aggressiveness were apparent between species. This study provides the first survey of Diaporthe species associated with blueberry twig blight and dieback in Portugal. It disclosed the occurrence of a diverse assemblage of Diaporthe species, whose status and impact as pathogens of blueberry is not yet fully understood.